Uptake of Breast Screening is Influenced by Current Religion and Religion of Upbringing - O'Reilly, Dermot (Journal of religion and health, 2013)
Research has shown that individuals with a current religious affiliation are more likely to use preventive health services. The aim of this study was to determine whether breast screening uptake in Northern Ireland is higher amongst women with a current affiliation to an organised religion and, for those with no current affiliation, to examine whether their religion of upbringing is associated with uptake of breast screening. The Northern Ireland Longitudinal Study (NILS) was used to link Census and national breast screening data for 37,211 women invited for routine breast screening between 2001 and 2004. Current religious affiliation, religion of upbringing and other demographic and socio-economic characteristics were as defined on the Census form. Multivariate logistic regression was used to determine the relationship between religion affiliation and attendance. Uptake of breast screening is about 25% lower for those without a current religious affiliation. There are modest differences between Catholics and Protestants, with the latter about 11% more likely to attend for screening. For those with no current religion, the religion of upbringing appears to positively influence attendance rates. These differences remain after adjustment for all of the socio-demographic and socio-economic factors that have been shown to influence uptake rates of breast screening in the UK to date. Record linkage is an efficient way to examine equity across demographic characteristics that are not routinely available. The lower uptake amongst those with no religious affiliation may mean that screening services may find it difficult to maintain or improve uptake rate in an increasingly secularised society.